2016
DOI: 10.1002/jbio.201600151
|View full text |Cite
|
Sign up to set email alerts
|

Second generation slit‐based photoacoustic tomography system for vascular imaging in human

Abstract: Slit-based photoacoustic tomography is a newly developed technique that improves the elevation numerical aperture of a linear array through acoustic diffraction. The slit, placed at the acoustic focus of a linear array, effectively forms an array of virtual detectors with high receiving angle, which subsequently improves the elevation resolution. However, due to the complex implementation, our original system could only image phantoms and sacrificed animals. In this report, the system has been significantly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…They demonstrated that the slit greatly diffracts the acoustic wave and increases the acoustic numerical aperture in the elevational direction. As a result, they improved the elevation resolution to 330 lm, which is close to the lateral resolution of 298 lm and enhanced the SNR by about four times [79,80]. Unlike pulse-echo US signals, PA signals have a very broad bandwidth, ranging from 1 to 100 MHz [82].…”
Section: Current Issues and Future Outlooksmentioning
confidence: 65%
“…They demonstrated that the slit greatly diffracts the acoustic wave and increases the acoustic numerical aperture in the elevational direction. As a result, they improved the elevation resolution to 330 lm, which is close to the lateral resolution of 298 lm and enhanced the SNR by about four times [79,80]. Unlike pulse-echo US signals, PA signals have a very broad bandwidth, ranging from 1 to 100 MHz [82].…”
Section: Current Issues and Future Outlooksmentioning
confidence: 65%
“…Commercially available ultrasound probes, such as L7-4 linear array (Philips, Netherlands), can achieve enhanced elevational resolution by adding cylindrically focusing acoustic lenses. In addition to the acoustic field focusing approach, Wang et al proposed an alternative elevational resolution enhancement method based on a thin slit [112,113]. In their setup shown in figures 35(a) and (b), a slit was placed at the acoustic focus of the detector array, which can make directional acoustic signals non-directional after diffraction and enhance the elevational resolving ability of the system.…”
Section: Elevational Resolution Enhancementmentioning
confidence: 99%
“…In addition to the imaging speed, recent advances in PACT also include compact laser systems [19], improved SNR and elevational resolution [126,127], low-cost light sources [128][129][130][131][132], and high-speed multispectral excitation [22,112,133,134]. Together, these advances have greatly enhanced PACT's imaging performance, especially in pre-clinical applications, and enabled a variety of biomedical studies by simultaneously providing large field of view, extended imaging depth, high imaging speed, functional and molecular sensitivity.…”
Section: Structural Patmentioning
confidence: 99%